Enhancing Molecular n‐Type Doping of Donor–Acceptor Copolymers by Tailoring Side Chains - Liu, Jian; Qiu, Li; Alessandri, Riccardo; Qiu, Xinkai; Portale, Giuseppe; Dong, JingJin; Talsma, Wytse; Ye, Gang; Sengrian, Aprizal Akbar; Souza, Paulo C. T.; Loi, Maria Antonietta; Chiechi, Ryan C.; et al. (Advanced materials (Weinheim), 2018)
In this contribution, for the first time, the molecular n‐doping of a donor–acceptor (D–A) copolymer achieving 200‐fold enhancement of electrical conductivity by rationally tailoring the side chains without changing its D–A backbone is successfully improved. Instead of the traditional alkyl side chains for poly{[N,N′‐bis(2‐octyldodecyl)‐naphthalene‐1,4,5,8‐bis(dicarboximide)‐2,6‐diyl](NDI)‐alt‐5,5′‐(2,2′‐bithiophene)} (N2200), polar triethylene glycol type side chains is utilized and a high electrical conductivity of 0.17 S cm−1 after doping with (4‐(1,3‐dimethyl‐2,3‐dihydro‐1H‐benzoimidazol‐2‐yl)phenyl)dimethylamine is achieved, which is the highest reported value for n‐type D–A copolymers. Coarse‐grained molecular dynamics simulations indicate that the polar side chains can significantly reduce the clustering of dopant molecules and favor the dispersion of the dopant in the host matrix as compared to the traditional alkyl side chains. Accordingly, intimate contact between the host and dopant molecules in the NDI‐based copolymer with polar side chains facilitates molecular doping with increased doping efficiency and electrical conductivity. For the first time, a heterogeneous thermoelectric transport model for such a material is proposed, that is the percolation of charge carriers from conducting ordered regions through poorly conductive disordered regions, which provides pointers for further increase in the themoelectric properties of n‐type D–A copolymers. Significantly enhanced molecularly doping of an n‐type donor–acceptor (D–A) copolymer by rationally tailoring its side chains without changing its donor–acceptor character is demonstrated. Polar triethylene‐glycol‐based side chains on the host greatly increase the solubility of dopant molecules in the host matrix with respect to the traditional alkyl side chains. The former gives a highest conductivity of 0.17 S cm−1 for D–A copolymers, representing a 200‐fold enhancement compared to the latter.